2006
DOI: 10.1016/j.physletb.2006.05.049
|View full text |Cite|
|
Sign up to set email alerts
|

Schwinger model in noncommutating space–time

Abstract: The 1 + 1 dimensional bosonised Schwinger model has been studied in a noncommutative scenario. The theory in the reduced phase space exhibits a massive boson interacting with a background. The emergence of this background interaction is a novel feature due to noncommutativity. The structure of the theory ensures unitarity and causality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Hence, Schwinger model can be a toy model to understand the quark confinement. The extension of the Schwinger model to the noncommutative version as regards different aspects has been addressed in [9,[11][12][13][14][15][16]. Here, we focus on the dynamical mass generation in the noncommutative space.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Schwinger model can be a toy model to understand the quark confinement. The extension of the Schwinger model to the noncommutative version as regards different aspects has been addressed in [9,[11][12][13][14][15][16]. Here, we focus on the dynamical mass generation in the noncommutative space.…”
Section: Introductionmentioning
confidence: 99%
“…Also, unitarity no longer requires (1.5) if a proper quantization is applied [19]. As a result, the theories with θ 0i = 0 have become an area of active research (see [20][21][22][23][24] for a non-exhaustive list of related works dealing with different aspects of time-space noncommutativity). Therefore it is natural that the properties of wave propagation with non-zero θ 0i should be considered too.…”
Section: Introductionmentioning
confidence: 99%
“…• d=2 : There are several papers on the study of noncommutative extension of the Schwinger model and its bosonized version, e.g., Refs. [20,21,24,27], where in [24,27], it is shown that the Schwinger mass, µ 2 = e 2 π , remains unchanged and does not receive any noncommutative corrections.…”
Section: Noncommutative Casementioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19]. Since the Schwinger model has played an important part as a QCD 4 toy model, naturally it was analyzed in many contexts by the introduction of spacetime noncommutativity, unveiling interesting properties of noncommutative QED 2 [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%